2015
DOI: 10.1007/s11664-015-3821-6
|View full text |Cite
|
Sign up to set email alerts
|

A New nBn IR Detection Concept Using HgCdTe Material

Abstract: This paper presents a new HgCdTe-based heterostructure to perform quantum infrared detection. The structure is based on the unipolar barrier concept, introduced by White in the 1980s for HgCdTe. The driving concept is the use of a large gap barrier layer to impede the flow of majority carriers (electrons on the conduction band in the case of n-type material) while facilitating the transport of minority (photo) carriers (holes on the valence band). The issue encountered here is the formation of a small potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 8 publications
1
9
0
2
Order By: Relevance
“…13 In HgCdTe material, proper p-type doping of the barrier reduces the valence band-offset and increases the offset in the conduction band. [14][15][16][17] The device with the barrier only in the conduction band is similar to that proposed in Ref. 1 in which a p-type barrier is interposed between two narrow gap n-type regions.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…13 In HgCdTe material, proper p-type doping of the barrier reduces the valence band-offset and increases the offset in the conduction band. [14][15][16][17] The device with the barrier only in the conduction band is similar to that proposed in Ref. 1 in which a p-type barrier is interposed between two narrow gap n-type regions.…”
Section: Introductionsupporting
confidence: 67%
“…[14][15][16][17] This paper presents the status of MOCVD-grown HgCdTe barrier detectors, with emphasis on technological achievements in removing the valence band offset made recently at the Institute of Applied Physics, Military University of Technology (MUT).…”
Section: Introductionmentioning
confidence: 99%
“…The development of nBn detectors based on HgCdTe grown by molecular beam epitaxy (MBE) is of interest because of the significant technological advantages over popular matrix photodiodes based on MBE HgCdTe, in which p-n junctions are usually created using a defect-forming ion implantation procedure [4]. Attempts at practical implementation of nBn detectors based on MBE HgCdTe are still few in number [5][6][7]. Recently, it was shown that it is possible to create medium-wavelength (3-5 μm, MWIR) MBE HgCdTe nBn detectors for which dark currents limited by hole diffusion were observed in the temperature range of 180-300 K [8].…”
mentioning
confidence: 99%
“…Создание nBn-детекторов на основе HgCdTe, выращенного методом молекулярнолучевой эпитаксии (МЛЭ), вызывает интерес из-за значительных технологических преимуществ перед популярными матричными фотодиодами на основе МЛЭ HgCdTe, в которых для формирования p−n-переходов обычно используется дефектообразующая процедура ионной имплантации [4]. Попытки практической реализации nBn-детекторов на основе МЛЭ HgCdTe пока немногочисленны [5][6][7]. Недавно показана возможность создания средневолновых (3−5 µm, MWIR) nBn-детекторов на основе МЛЭ HgCdTe, для которых в диапазоне температур 180−300 K наблюдались темновые токи, ограниченные диффузией дырок [8].…”
unclassified